Tatalaksana Praktis Gangguan Haid di Praktek Sehari-hari - Fatimah Usman (Conferences of Medical Sciences Dies Natalis, 2019)
Menstrual disorders are the most common disorders in women of childbearing age and the most common complaint in gynecological outpatient practices in several hospitals. Besides disrupting activities, menstrual disorders can be a serious problem as a life threatening condition. Menstrual disorders can be divided based on the duration and the etiology. Based on the duration of occurrence, acute and chronic can be distinguished. Etiology can be distinguished based on abnormal uterine bleeding criteria (PALM-COEIN). The management of this kind of disorder depends on the type of cause of abnormal uterine bleeding. Surgical and non-surgical management can be used as an option in the treatment of menstrual disorders. Hormonal therapy options are the most popular treatment options at present with minimal side effects and relatively affordable prices. Management of abnormal uterine bleeding aims to improve the general condition, stop bleeding, and restore the function of reproductive hormones. Stopping bleeding can be done with medical, dilatation and curettage, as well as operative measures.